Cambridge English for human resources - Sandford, George (Professional english (Cambridge), 2011)
Cambridge English for Human Resources covers a wide range of topics of concern to human resources and personnel development, from understanding the essentials of resourcing and outsourcing through to strategic HR. The ten standalone units allow learners to focus on the areas of HR and Personnel Development most important to them. As well as teaching the specialist vocabulary and theory of HR, the course also develops job-specific skills such as coaching, designing and implementing appraisal systems, managing conflict and others. Thanks to the Audio CD that includes the complete listening material from the Student's Book the course is ideal for both self-study and classroom teaching. The course requires no specialist knowledge on the part of the teacher as free comprehensive teacher's notes are available online